Islamic business development of Madurese-owned ethnic-based grocery stores: Study from Indonesia - Zainal Abidin; Sakinah; Farid Firmansyah; Moch Cholid Wardi; Rudy Haryanto; Sri Handayani; Zaenuddin Hudi Prasojo (Cogent Economics & Finance, 2023)
The retail grocery business is experiencing rapid expansion in several major Indonesian cities. A significant proportion of these establishments is owned and managed by a particular ethnic group, specifically the Madurese community hailing from East Java, who take pride in their identity as Muslim entrepreneurs. This research endeavors to investigate the fundamental factors contributing to the sustainability and expansion of Madurese-owned Muslim-run grocery stores as ethnic-based grocery stores (EGS). The data for this study were acquired through observations and in-depth interviews with key figures among EGS owners and staff. The findings highlight that the pivotal strategy for the success and growth of EGS lies in their capacity to adapt and emulate modern retail outlets. Furthermore, the principles of cooperation, familial bonds, cultural preservation, and adherence to Islamic values that have been fostered within the Madurese Muslim ethnic groups residing in urban environments play a significant role. Additionally, the distinctive relationships between store proprietors and employees contribute significantly to the swift proliferation of EGS across Indonesia.
Keywords: 330; ethnic-based grocery store; Islamic business development; survival strategy transformation